Spaces of Care - Confronting Colonial Afterlives in European Ethnographic Museums - Modest, Wayne; Augustat, Claudia (Edition Museum, 2023)
Alarming environmental shifts and disasters have raised public awareness and anxieties regarding the future of the planet. While planetary in scale, the negative effects of this global crisis are distributed unequally, affecting some of the already most fragile communities most intensely, thus contributing to rising global inequality. The pairing of environmental crises and a sense of inadequacy facing hitherto celebrated models of citizenry informs a current spirit of the times. The contributors to this volume place ethnographic or world cultures museums at the centre of these debates - these museums have been embroiled in longstanding debates about their histories, collections, and practices in relation to the colonial past.